Sertifikasi Halal dan Sertifikasi Non Halal pada Produk Pangan Industri - Asep Syarifuddin Hidayat; Mustolih Siradj (Universitas Islam Negeri Jakarta, 2015)
As a commodity, food has a very large role in improving national food image in the international community and foreign exchange at the same time. However, food safety must be considered seriously. The enactment of Act Halal Product Guarantee (UUJPH) aims to provide comfort, security, safety, and the certainty of availability of halal products for people to consume and use the products; moreover, people get peace in consuming and using those goods. Certification and labelling on food products are a measurement and controlling, so it avoids consumers’ determination and dangers.DOI: 10.15408/ajis.v15i2.2864